The interaction effect of government non-financial support and firm's regulatory compliance on firm innovativeness in Sub Saharan Africa - Sam Z. Njinyah; Simplice Asongu; Bosede Ngozi Adeleye (African Governance and Development Institute (AGDI), 2022)
Firms' regulatory compliance with environmental and safety issues has been suggested as one of the reasons why firms innovate. Such compliance provides legitimacy, improves reputation and corporate image, and enhances customer loyalty and competitive advantages, which influences firm innovativeness. However, regulatory compliance is costly and with limited resources, the role of government support is crucialas a moderator, to help firms become more compliant and influence their innovativeness. The study uses data from the World Bank Enterprise Innovation Survey for seven countries in Sub Saharan Africa. Regulatory compliance has a positive and significant effect on firm innovativeness. Increased use of government non-financial support enhances the level of firm regulatory compliance and the effect of regulatory compliance on firm innovativeness. The study contributes to the literature on compliance and firm innovativeness in Africa by showing how the positive effect of regulatory compliance on firm innovativeness is stronger when firms benefit from government non-financial support.
Keywords: 330; Regulatory Compliance; Firm Innovativeness; government non-financial Support; Sub Saharan Africa (SSA)